Anti-obesity study of Elateriospermun tapos Blume hot aqueous extract in high-fat diet sprague-dawley rats - Ja'afar, Nor Liyana (2018)
Obesity is a major public health burden and currently became a global pandemic. Current pharmacotherapy often accompanied with myriads of adverse side effects thus, the search for a safer novel cure is crucial. This study focus on the protective effects of Elateriospermum tapos extract on rats fed with high-fat diet and its potential as an anti-obesity agent through inhibition of lipoprotein lipase (LPL) and triglyceride (TG) absorption. Thirty-six male Sprague-Dawley rats were allocated to negative control group (NC) fed with normal diet, while positive control (PC), drug control (DC), and treatment groups (T10, T100 and T200) were fed with high-fat and cafeteria diet. The DC group was given orlistat of 10mg/kg bodyweight and treatment groups were supplemented with 10, 100 and 200mg/kg bodyweight of E. tapos shell extract respectively. The bodyweight and caloric intake were measured weekly. After 4 weeks, the rats were euthanized and the plasma, liver and retroperitoneal white adipose tissues (RpWAT) were collected for biological assays of TG, LPL and plasma lipid profiles. Liver and adipose tissues were stained with Haematoxylin & Eosin for histological analysis. The PC group had significantly (p<0.05) higher in bodyweight, caloric intake and weight of RpWAT compared to NC group. The extract significantly (p<0.05) lowered the bodyweight and the weight of fat depots in treatment groups as compared to PC group. Nonetheless, the E. tapos shell extract supplementation has no positive inhibiting effects on the tissues TG and LPL level. Further, only T100 group had significantly (p<0.05) lowered plasma TG level as compared to PC. The size of both hepatocytes and adipocytes of supplemented groups were significantly (p<0.05) smaller as compared to those in obese group. Based on the findings, this study suggests that supplementation of E. tapos shell extract exhibited preventive effects on high-fat and cafeteria diet-induced obesity in rats. The extract however has no potential in the inhibition of TG and LPL level.